Spatiotemporal distribution and environmental risk assessment of 6PPDQ in the Schuylkill River - Kavya Somepalli; Gangadhar Andaluri (Emerging Contaminants, 2025)
Tire wear particles (TWPs) and associated contaminants, including microplastics, benzothiazoles, polycyclic aromatic hydrocarbons (PAHs), N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6PPD), its byproduct 6PPD-Quinone (6PPDQ), and heavy metals, are emerging pollutants in aquatic ecosystems. 6PPD, a commonly used tire antioxidant, reacts with ozone to form 6PPDQ, a toxic compound linked to acute mortality in aquatic species, such as Coho salmon. Despite its known impact, data on 6PPDQ in northeastern U.S. freshwater systems, including the Schuylkill River, remain limited. This study examined the spatiotemporal distribution of 6PPDQ in the Schuylkill River and assessed its environmental risks. It also identified key contamination sources and seasonal trends. We analyzed 6PPDQ concentrations at 16 locations across different seasons using the EPA 1634 Draft Method. Their relationship with traffic volume, population density, and tire-related industrial proximity was evaluated. Concentrations ranged from non-detectable to 17.95ng/L, with urban regions exhibiting higher levels. A moderate positive correlation (r=0.416) between 6PPDQ concentrations and Average Annual Daily Traffic (AADT) suggests traffic as a significant source. Population density and industrial proximity also contributed to contamination. Based on the EPA freshwater screening value (11ng/L), two sites posed high risks, while 88% were at medium risk. Risk levels peaked in October, when increased precipitation and reduced flow exacerbated contamination. These findings highlight the seasonal intensification of 6PPDQ pollution, emphasizing the need for stormwater management and long-term monitoring to mitigate risks and assess seasonal dynamics in freshwater systems.